2011
DOI: 10.1007/s11033-011-0920-1
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Dahi containing Lactobacillus acidophilus and Bifidobacterium bifidum alleviates age-inflicted oxidative stress and improves expression of biomarkers of ageing in mice

Abstract: The potential benefiting effects of probiotic Dahi on age-inflicted accumulation of oxidation products, antioxidant enzymes and expression of biomarkers of ageing were evaluated in mice. Probiotic Dahi were prepared by co-culturing in buffalo milk (3% fat) Dahi bacteria (Lactococcus lactis ssp. cremoris NCDC-86 and Lactococcus lactis ssp. lactis biovar diacetylactis NCDC-60) along with selected strain of Lactobacillus acidophilus LaVK2 (La-Dahi) or combined L. acidophilus and Bifidobacterium bifidum BbVK3 (LaB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…The liver is the major site of glutathione synthesis and transport and thus could explain the apparent effects of LR consumption on GPx activity in liver and RBCs. Similarly, consumption of probiotic cultured milk has also been shown to enhance activities of SOD and CAT in various clinical and experimental studies (Shih and Yen 2007;Yadav et al 2008;Zhou et al 2010;Kaushal and Kansal 2012) which could be attributed to release of antioxidative peptides from milk proteins by proteolytic activity of probiotic strains. Moreover, it has also been shown that probiotic supplementation may protect against oxidative stress by decreasing the accumulation of ROS (Kullisar et al 2002;Martarelli et al 2011) possibly by mechanisms involving metal ion chelation, scavenging of the oxidant compounds, or even inhibiting ROS production in the intestine (Azcárate-Peril et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the major site of glutathione synthesis and transport and thus could explain the apparent effects of LR consumption on GPx activity in liver and RBCs. Similarly, consumption of probiotic cultured milk has also been shown to enhance activities of SOD and CAT in various clinical and experimental studies (Shih and Yen 2007;Yadav et al 2008;Zhou et al 2010;Kaushal and Kansal 2012) which could be attributed to release of antioxidative peptides from milk proteins by proteolytic activity of probiotic strains. Moreover, it has also been shown that probiotic supplementation may protect against oxidative stress by decreasing the accumulation of ROS (Kullisar et al 2002;Martarelli et al 2011) possibly by mechanisms involving metal ion chelation, scavenging of the oxidant compounds, or even inhibiting ROS production in the intestine (Azcárate-Peril et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Hutt et al (2009) reported that consumption of a synbiotic product reduced the systemic oxidative stress due to colonization of Helicobacter pylori. Kaushal and Kansal (2012) reported that probiotic dahi containing L. acidophilus and B. bifidum reduces age-inflicted oxidative stress as studied by expression of biomarkers of ageing in mice. Moreover, results of revealed that synbiotic yogurt samples containing L. plantarum and L. fermentum, the DPPH radical inhibition was 85 and 82 %, respectively, at day 1 and the values increased as the storage time increased.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolites produced by the action of probiotics on milk constituents also possess immuno-stimulating potentials (Cavallo et al 1996). Recent studies showed that administration of Dahi prepared using these strains protects against enteric infection and gastrointestinal carcinogenesis Kansal 2008, 2009), and ameliorates age related oxidative stress and molecular alterations in mice (Kaushal and Kansal 2011). The present study was conducted to examine the effect of probiotic Dahi prepared using these strains on age related decline in macrophage phagocytic functions in mice.…”
Section: Introductionmentioning
confidence: 96%